(untitled) (Swiss Medical Weekly, 2011)
Inflammatory responses in the liver – a central constituent of hepatic wound healing – can be self-limited or persistent depending on the aetiology, liver health state, concentration of toxins or pathogens, and the time frame of exposure to toxins or infection. In case the immune system eradicates a pathogen or in case toxin-exposure is transient, acute hepatitis resolves and the affected liver tissue regenerates ad integrum. However, in many cases liver damage remains chronic. Irrespective of the aetiology, chronic liver damage drives chronic hepatitis and hepatocyte death as well as compensatory proliferation, reflecting liver regeneration. Over time this potentially promotes further hepatic damage, fibrosis, cirrhosis and liver cancer. Here, we review the current knowledge on how chronic liver injury and inflammation is triggered and maintained, and how inflammation is linked to liver cancer. We also discuss the most frequently used animal models for damage or inflammation induced liver cancer and their suitability for conducting clinically relevant research. Summary Hepatitis can be elicited in response to a plethora of diverse insults to the liver. Chronic inflammation is associated with persistent liver damage and consecutive regeneration, potentially leading to fibrosis and cirrhosis and the development of HCC. Human HCC, even of the same aetiology, reveal a broad clinical, morphological and molecular spectrum, however, they generally have a bad prognosis. The efficiency of drugs is currently limited, but might be improved by the identification of specific molecular targets. Several mouse models are available which are used to recapitulate different aetiologies of human hepatocarcinogenesis. It is now of paramount importance to determine how these models are transferable to human HCC and how they can be thus exploited for interventional studies. Acknowledgments: We thank Jay Tracy, Barbara Zadnich, Sukumar Namineni, Dr. Nicole Simonavicius and Dr. Barbara Stecher for reading the manuscript and for valuable input. We are thankful to all members of our laboratory for discussions and apologise to those authors whose contributions were not cited due to space limitations.